СПІВВІДНОШЕННЯ НАУКИ ТА ФІЛОСОФІЇ В КОНТЕКСТІ ФІЛОСОФІЇ НАУКИ - Лаута, О. Д. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Стаття присвячена дослідженню співвідношення науки та філософії в контексті філософії науки. Маючи спільний раціонально-теоретичний підхід до вивчення світу та науки, вони відрізняються пред- метом пізнання. Специфіка філософії науки полягає у розумінні науки як цілісного феномену, тобто в єдності усіх різноманітних її проявів, у виявленні її місця в структурі картини світу та поясненні поте- нціалу для формування подальших стратегій розвитку. Лаута Е.Д. Соотношение науки и философии в контексте философии науки. Статья посвяще- на исследованию соотношения науки и философии в контексте философии науки. Имея общий рацио- нально-теоретический подход к изучению мира и науки, они отличаются предметом познания. Специфи- ка философии науки заключается в понимании науки как целостного феномена, то есть в единстве всех разнообразных ее проявлений, в выявлении ее места в структуре картины мира и объяснении потенциала для формирования последующих стратегий развития. Ключевые слова: философия, наука, философия науки, гносеология, эпистемология, методология. О. Lauta. Interaction of science and philosophy at the context of philosophy of science. The interrelations between philosophy and science are very complicated problem accumulating the experience with many branches and aspects: historical, world outlook, axiological, epistemological and methodological. This is result of creative activity of many generations of researches including many layers of knowledge. Philosophy of science as academic discipline adapts all mentioned above to the tasks of system of education. This is the answer for the needs of social subject. On one side, progress of material and spiritual production is not possible without active use of scientific knowledge. On other side, such the needs are caused by complicated and many aspect character of science and by the task of deep accumulation of already existing experience of researches results use, which is important and necessary to be generalized, systematized and implemented as the subject of studies and academic discipline. Thus, philosophy of science as branch of research is both objective result of culture and science development and necessary factor of their further development. The article is devoted to interaction of science and philosophy at the context of philosophy of science. Despite of sharing the same rational theoretical approach to research of world and science they have different object of cognition. The main specifics of philosophy of science is its understanding of science as integral phenomenon with unity of all its variable manifestations as well as reveal of its place in general theoretical picture of world and potential for further development strategies. Keywords: philosophy, science, philosophy of science, gnoseology, epistemology, methodology.